Fusion status in patients with lymph node‐positive (N1) alveolar rhabdomyosarcoma is a powerful predictor of prognosis: Experience of the European Paediatric Soft Tissue Sarcoma Study Group (EpSSG). Issue 15 (24th May 2018) - Gallego, Soledad; Zanetti, Ilaria; Orbach, Daniel; Ranchère, Dominique; Shipley, Janet; Zin, Angelica; Bergeron, Christophe; de Salvo, Gian Luca; Chisholm, Julia; Ferrari, Andrea; Jenney, Meriel; Mandeville, Henry C.; et al.
Abstract : BACKGROUND: Alveolar rhabdomyosarcoma (aRMS) with lymph node involvement (N1 classification) accounts for up to 10% of all cases of RMS. The prognosis is poor, and is comparable to that of distant metastatic disease. In the European Paediatric Soft Tissue Sarcoma Study Group (EpSSG) RMS2005 protocol, patients with a histologic diagnosis of aRMS/N1 received intensified chemotherapy with systematic locoregional treatment. METHODS: Patients with aRMS/N1 were enrolled prospectively after primary surgery/biopsy and fusion status was assessed in tumor samples. All patients received 9 cycles of induction chemotherapy and 6 months of maintenance therapy. Local treatment included radiotherapy to the primary site and lymph nodes with or without secondary surgical resection. RESULTS: A total of 103 patients were enrolled. The clinical characteristics of the patients were predominantly unfavorable: 90% had macroscopic residual disease after initial surgery/biopsy, 63% had locally invasive tumors, 77% had a tumor measuring >5 cm, and 81% had disease at unfavorable sites. Fusion genes involving forkhead box protein O1 ( FOXO1 ) were detected in 56 of 84 patients. Events occurred in 52 patients: 43 developed disease recurrence, 7 had disease that was refractory to treatment, and 2 patients developed second neoplasms. On univariate analysis, unfavorable disease site, tumor invasiveness, Intergroup Rhabdomyosarcoma Study group III, and fusion‐positive status correlated with worse prognosis. The 5‐year event‐free survival rate of patients with fusion‐positive tumors was 43% compared with 74% in patients with fusion‐negative tumors ( P  = .01). On multivariate analysis, fusion positivity and tumor invasiveness proved to be unfavorable prognostic markers. CONCLUSIONS: Fusion status and tumor invasiveness appear to have a strong impact on prognosis in patients with aRMS/N1. Fusion status will be used to stratify these patients in the next EpSSG RMS study, and treatment will be intensified in patients with fusion‐positive tumors. Cancer 2018. © 2018 American Cancer Society . Abstract : Fusion status will be incorporated in the new stratification of patients with alveolar rhabdomyosarcoma and lymph node involvement in future European Paediatric Soft Tissue Sarcoma Study Group (EpSSG) studies. Patients with fusion‐positive tumors and lymph node involvement will receive intensified treatment in the next EpSSG rhabdomyosarcoma trial.